EFICIÊNCIA E EFEITO RESIDUAL DE INSETICIDAS APLICADOS EM DIFERENTES SUPERFÍCIES PARA O CONTROLE DE BLATTELLA GERMANICA (LINNAEUS, 1767) (DICTYOPTERA: BLATTELLIDAE) - Parreira, R.s. [UNESP]; Ferreira, M.c. [UNESP]; Martinelli, N.m [UNESP]; Silva, I.c. [UNESP]; Pazini, W.c. [UNESP] (Instituto Biológico, 2020)
The aim of the present study was to evaluate the efficiency and residual effect of insecticides applied on tiles and slate for the control of Blattella germanica. The experiment was carried out in the Departamento de Fitossanidade, UNESP Jaboticabal, SP, Brazil, (May 3 to August 5, 2007). The population susceptible to chemical control was grown in a nonclimatized room. The treatments were lambda-cyhalothrin (Demand 2,5CS) 10 mL/L (12,5 mg/m2); lambda-cyhalothrin (Icon 5,0 CE) 5 mL/L (12,5 mg/m2); deltamethrin (Deltagard WG) 2 sachets/10 L (12,5 mg/m2); lambda-cyhalothrin (Zeon 50CS) 5 mL/L (12,5mg/m2); deltamethrin (Deltek CS) 5 mL/L (6,25 mg/m2); dichlorvos (DDVP 1000CE) 5 mL/L (250 mg/m2) and a control plot. The experimental design consisted of randomized blocks with four replicates. Insecticides were sprayed with a pressurized sprayer (350 kPa) at a volume of 40 mL/m2. After 1h, 10 adult German cockroaches were plotted over the treated area and stayed there for 15 min. They were then transferred to pots for evaluations (0, 1, 2, 4, 24, 48 and 72 h after exposition). Treated plates were kept on shelves to evaluate the residual effect of products 30, 60 and 90 days after application. Data was submitted to analysis of variance and Tukey test. The efficiency was calculated. It was concluded that on the application of insecticides there is no difference between the surfaces in the control of B. germanica. The residual effect was greater on a tiled surface in relation to slate. The insecticides lambda-cyhalothrin and deltamethrin (WG) resulted in sufficient control up to 90 days after the spraying.

Objetivou-se avaliar eficiência e efeito residual de inseticidas aplicados sobre azulejo (face lisa) e ardósia (rugosa) para o controle de Blattella germanica. Realizou-se o experimento no Departamento de Fitossanidade, UNESP-Jaboticabal, SP (de 3-5 a 2-8-2007). A população suscetível ao controle químico foi criada em sala não climatizada. Os tratamentos utilizados foram (dosagens em produtos comerciais): lambdacialotrina (Demand 2,5 CS) 10 mL/L (12,5 mg/m2); lambdacialotrina (Icon 5,0 CE) 5 mL/L (12,5 mg/m2); deltametrina (Deltagard WG) 2 saches/10 L (12,5 mg/m2); lambdacialotrina (Zeon 50CS) 5 mL/L (12,5 mg/m2); deltametrina (Deltek CS) 5 mL/L (6,25 mg/m2); Diclorvos (DDVP 1000CE) 5 mL/L (250 mg/m2) e testemunha. O delineamento experimental utilizado foi blocos casualizados, com quatro repetições. Os inseticidas foram aplicados com pulverizador pressurizado (350 kPa) e volume de 40 mL/m2. Uma hora após a aplicação, liberaram-se 10 baratas adultas para caminhar sobre a área tratada. Após 15 minutos foram retiradas e colocadas em potes para avaliações (0, 1, 2, 4, 24, 48 e 72 horas após a exposição). Placas tratadas foram mantidas em prateleiras para avaliar o efeito residual dos produtos 30, 60 e 90 dias após aplicação. Os dados foram submetidos à análise de variância e teste Tukey. Concluiu-se que no dia da aplicação dos inseticidas não ocorre diferença entre as superfícies no controle de B. germanica. O efeito residual dos inseticidas foi maior na superfície lisa (azulejo) do que na superfície rugosa (ardósia). Os inseticidas lambdacialotrina e deltametrina (WG) proporcionaram excelente controle de B. germanica, até 90 dias após a aplicação.
EFFICIENCY AND RESIDUAL EFFECT OF INSECTICIDES APPLIED ON DIFFERENT SURFACES FOR THE CONTROL OF BLATTELLA GERMANICA (LINNAEUS, 1767) (DICTYOPTERA: BLATTELLIDAE)
Keywords: German cockroac; urban pest management; urban pest control; Barata alemã; manejo de pragas urbanas; tratamento domissanitário